FRACTURE FAILURE ANALYSIS IN SNAP-THROUGH INDUCED MULTISTABLE SANDWICH STRUCTURES WITH BLAST LOADING VARIATIONS - Maulana, Dede
The development of structural technology in vehicles has continued to increase rapidly over the last few years, one of which is in the combat vehicles. Combat vehicles require a structure that is resistant to blast impact for the safety of passengers. One of structure that has potential advantages for use is Snap-through Induced Multistable Sandwich Structures. This structure uses a multi-stable beam as a core which has a good ability to absorb impact energy due to blast. In this research, studies and simulations were carried out to obtain the response of Snap-through Induced Multistable Sandwich Structures to variations in blast loading. The blast load model used is Load Blast Enhanced (LBE) with blast load variations of 8 kg, 10 kg and 11 kg. Apart from variations in blast loading, other simulations were also carried out, configuration variations (Configuration I and II) and material failure variations (Johnson-Cook, Cockroft-Latham, and Piecewise Linear Plasticity). In the final simulation, an element deletion method was added to determine the failure process that occurred in the structure. Based on the simulation analysis, the optimum energy absorption results were Configuration II using the Johnson-Cook method of 5,3 kJ/kg (TNT = 8 Kg), 6,89 kJ/kg (TNT = 10 Kg) dan 7,69 kJ/kg (TNT = 11 Kg). In this simulation, no failures were found. Additional simulations using element deletion show that fracture failure occurs in the joint between frame and multistable beam.